Evaluation of the metabolic burden of heterologous protein production in Saccharomyces cerevisiae - Görgens, Johann Ferdinand (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1999.